Prevalence of vision loss in high-income countries and in Eastern and Central Europe in 2020: magnitude and temporal trends - Bron, Alain; Jonas, Jost B. (Ophthalmic epidemiology, 2025)
To estimate the prevalence of vision loss for 2020 in high-income countries (HICs) and Central/Eastern Europe and analyse evolving trends since 1990. Based on a systematic review of medical literature, prevalence of blindness, moderate and severe vision impairment (MSVI), mild vision impairment (VI), moderate VI and presbyopia were estimated for 1990, 2000, 2010, and 2020. The study included 68 population-based studies. In the whole study region, the age-standardized prevalence (all ages) of blindness, MSVI, moderate VI, severe VI, mild VI, and presbyopia-related VI was 0.17% (95% CI:0.15-0.19), 2.27% (2.05-2.49), 2.06% (1.84-2.29), 0.21% (0.18-0.23), 1.79% (1.62-1.99), and 2.61% (1.88-3.48) respectively, with slightly higher rates for women than men. The prevalence rates were higher in Central/Eastern Europe than in the HIC, and lower than the global rates. Stratified between Australasia, high-income Asia Pacific region, high‐income North America, Western Europe, Central Europe, and Eastern Europe, the age-standardized prevalence of blindness changed between 2000 and 2020 for men aged 50+ years by −7.95% (−8.11/−7.78), −14.51% (−14.64/−14.38), +13.18% (+13.00/+13.36), −12.07% (−12.23/−11.91), −14.39% (−14.54/−14.23), and −23.59% (−23.72/−23.46), respectively, without significant sex-related differences. Highest increase was in high‐income North America (+13.18% (+13.00/+13.36)) and most marked reduction in Eastern Europe (−23.59% (−23.72/−23.46)). Estimated blind individuals were stratified as follows: Australasia, 68,866 (54,913-84,527), high-income Asia Pacific region, 535,124 (439,912-640,330), high‐income North America, 711,990 (575,977-867,402), Western Europe, 1,533,752 (1,218,371-1,898,343), Central Europe, 327,352 (264,513-398,083) and Eastern Europe, 789,618 (663,130-923,121). Age-standardized prevalence of blindness and MSVI have further decreased in HIC and Eastern/Central Europe (except for high‐income North America with an increase).
Mitglieder der Vision Loss Expert Group of the Global Burden of Disease Study & the GBD 2019 Blindness and Vision Impairment Collaborators: Jost B. Jonas [und viele mehr]
Gesehen am 20.10.2025